La investigación y la prueba de contextocomo elementos de política criminal parala persecución del crimen organizado - Luis Orlando Toro Garzón; Mónica María Bustamante Rúa (Revista Criminalidad)
The problem addressed by the article is directly related to the reflection about what is the incidence of research and context evidence as elements of criminal policy to prosecute the organized crime. We drew as first objective to make a reflective approach to the concepts of organized crime, context investigation, context evidence and criminal policy, to then develop as a second objective, its correlation from its implementation in the Inter - American Court of Human Rights and, in the Colombian case, from the context investigation modality and its derived proof. As a third objective, we sought to establish the viability from the legal and constitutional scope and with a criminal policy approach to the application of this methodology and context evidence for the prosecution of the organized crime as State’s response strategy. The research approach is qualitative, which contains exploratory, descriptive, analytic and propounding research. As main result is the need for the criminal policy of the Colombian State to consolidate the application of the context investigation and, in particular, to define the way in which its products will be incorporated into the body of evidence, that is, if the results obtained in the construction of research contexts can be treated as an autonomous means of evidence with characterization and designation of context evidence.